2018
DOI: 10.1042/bsr20170730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and safety of Reteplase and Alteplase in the treatment of hyper-acute cerebral infarction

Abstract: Objective: The present study aimed to investigate the efficacy and safety of Reteplase (rPA) and Alteplase (rt-PA) in the treatment of hyper-acute cerebral infarction (CI).Methods: Six hundred and eleven patients with hyper-acute CI selected from September 2014 to September 2016 were assigned into the aspirin, rt-PA, rPA, rt-PA + aspirin, and rPA + aspirin groups based on their willingness. The difference of efficacy in five groups were evaluated with National Institute of Health Stroke Scale (NIHSS), modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…According to the aggregated results of the current study, after treatment, the NIHSS score, cerebral hemodynamic index and T-lymphocyte level of the 2 groups were improved, but the clinical efficacy, NIHSS score, cerebral hemodynamic index and T-lymphocyte level of the observation group elicited greater effect than those of the control group ( P < .05), which was consistent with the results of Liu et al [ 12 ] and Lin et al [ 13 ] They suggested that the patients with acute stroke who were treated with the intravenous thrombolysis with alteplase and edaravone gained significant effect, which effectively improved the neurological function of patients, help patients recover the indexes of cerebral hemodynamics, and restore the level of T-lymphocytes to normal. The following factors might contribute to the abovementioned results:…”
Section: Discussionsupporting
confidence: 92%
“…According to the aggregated results of the current study, after treatment, the NIHSS score, cerebral hemodynamic index and T-lymphocyte level of the 2 groups were improved, but the clinical efficacy, NIHSS score, cerebral hemodynamic index and T-lymphocyte level of the observation group elicited greater effect than those of the control group ( P < .05), which was consistent with the results of Liu et al [ 12 ] and Lin et al [ 13 ] They suggested that the patients with acute stroke who were treated with the intravenous thrombolysis with alteplase and edaravone gained significant effect, which effectively improved the neurological function of patients, help patients recover the indexes of cerebral hemodynamics, and restore the level of T-lymphocytes to normal. The following factors might contribute to the abovementioned results:…”
Section: Discussionsupporting
confidence: 92%
“…The treatment efficacy was assessed according to the degree of NIHSS score reduction [ 16 ]. Cured was indicated if the patient could completely take care of himself/herself, with a reduction of NIHSS score ≥ 91%.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro experiment shows that reteplase has a faster clot lysis rate than alteplase [ 43 ]. However, clinical studies of reteplase treatment for AIS did not show any additional benefit in any aspect when compared with alteplase [ 12 , 44 ]. Our simulation results show that reteplase has the longest lysis time (100 min) and the lowest temporal concentration due to the sluggish reaction kinetics and shorter half-life than urokinase and tenecteplase.…”
Section: Discussionmentioning
confidence: 99%